(untitled) (Biological Sciences - PJSIR, 1995)
ThetraceelementsAg,Au,Co,Cr,Cu,Fe,K,Mg,Mn,Na,Ni,Pb,SrandZninfenugreekandlupin(leaves,stems, pods, pericarp, seeds,testa andcotyledon) aswell asin soilsamplestakenfromtheimmediate vicinity ofcrop roots at 10,30 and 60em depths intheGerf Husseinarea weredeterminedusing flame atomic absorption spectrophotometer. Ca andCl wereestimated by EDTA andClby ion selectiveelectrode.The results indicatedthat thetraceelements are present in high concentrations in the soil samplescollected from 60 cmdepth. In fenugreek and lupin, most elements areconcentrated in leavesand stems.The elementsCa,Cl,Co,Fe, Mg,Mn, KandZn arepresent in higherconcentra- tions in the crops as compared to the soil.